Associations between the timing of different foods’ consumption with cardiovascular disease and all-cause mortality among adults with sleep disorders - Zhang, Jia; Zhang, Yuntao; Liu, Lin; Wang, Xuanyang; Xu, Xiaoqing; Li, Ying; Han, Tianshu; Wei, Wei (Frontiers in Nutrition, 2022)
Introduction: People with sleep disorder are under disrupted biological rhythm, whether changing the timing of specific foods consumption contribute to decreasing cardiovascular and all-cause risk is unknown. Methods：A total of 8005 participants with sleep disorder were selected from the U.S. National Health and Nutrition Examination Survey from 2005 to 2014. Cox proportional hazards regression models were used to analyze the relationship between the consumption time of foods and cardiovascular disease and all-cause death. Moreover, equivalent food substitution models were carried out to evaluate the alterations in the risk of cardiovascular disease mortality for the changed food intake time. Results: After adjusting for multiple confounders, participants with consumption of red and orange vegetables, starchy vegetables and fermented dairy in the morning (HRred and orange vegetables=0.45, 95% CI:0.26-0.81; HRstarchy vegetables=0.47, 95% CI:0.25-0.88; HRfermented dairy=0.57, 95% CI:0.36-0.89), and milk and eggs in the evening contribute to reduce the likelihood of death from CVD (HRmilk=0.65, 95% CI:0.43-0.96; HReggs=0.92, 95% CI:0.53-0.99). Iso-calorically switching 0.1 serving of starchy vegetables, fermented dairy and milk intake from one period to another does significantly reduce the mortality risk of cardiovascular disease. Conclusions: Higher intake of red and orange vegetables, starchy vegetables and fermented dairy in the morning, milk and eggs in the evening confers a lower risk of cardiovascular disease among individuals with sleep disorder.